An Analysis of Metaphor in the Lyrics of Selected Minangkabaunese Songs - Deru Lukmana; Rusdi Noor Rosa; Leni Marlina (English Language and Literature, 2019)
Metaphor is two things of an implicit comparison which two unlike objects are compared with factual, the first is original meaning and the second is describing of metaphor. The purpose of this research is to analyze the types of metaphor using the theory of Lakoff and Johnson (1980). The researcher used descriptive method. The data were collected by downloading Minangkabaunese songs based on themes which fail in love or romance theme and rantau theme, listening them repeatedly, identifying and putting them into table. The data were also analyzed by classifying the data, analyzing the data, deciding the research findings, and drawing the conclusion. The result in this research there are 23 the data found in Minangkabaunese songs whose theme is fail in love or romance: structural (34,78%), orientational (39,13%), ontological (26,09%) and 25 the data found in Minangkabaunese songs whose theme is rantau: structural (56%), orientational (36%), ontological (8%). Therefore, a number of selected Minangkabaunese songs were dominated by both structural and orientational metaphor.